Категорійні значення в неелементарному простому реченні - Мірченко, Микола Васильович; Mirchenko, M. V. (Волин. нац. ун-т ім. Лесі Українки, 2011)
Стаття продовжує цикл публікацій автора з проблем функційно-категорійної граматики. Проаналізовано категорійні семантико-синтаксичні значення в неелементарному простому реченні. The article continues the sequel of publications of the author devoted to the problems of functional categorical grammar. Categorial semantic-syntactic meanings in the non-elementary simple sentence are analysed in the article.
Categorial Meanings in the Non-Elementary Simple Sentence.
Роботу виконано на кафедрі української мови ВНУ ім. Лесі Українки
Keywords: неелементарне речення; підкатегорія звертання; підкатегорія дуплексива; підкатегорія інструментального суб’єкта; підкатегорія предикатної субстанційності; the non-elementary sentence; the subcategory of address; the subcategory of duplexive; the subcategory of instrumental subject; the subcategory of predicative substantivity